2017
DOI: 10.1371/journal.pone.0183720
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aqueous extract of Xinjiang Artemisia rupestris L. (an influenza virus vaccine adjuvant) on enhancing immune responses and reducing antigen dose required for immunity

Abstract: Potent adjuvant can improve the effectiveness of vaccines and reduce the antigen doses required for initiating the protective immunity. In this study, we identified that aqueous extract of Artemisia rupestris L. (AEAR) could be employed as an efficient adjuvant for influenza virus vaccine (V) to enhance immune responses and reduce the antigen doses required for initiating immunity, without compromising the immune response. ICR mice were subcutaneously co-administrated with V combined with different concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Abundant Chinese medicinal formulae and Chinese patent medicine can effectively prevent healthy person from infection. As a number of studies have shown [12][13][14] , TCM can activate immune cells, improve phagocytosis and induce the production of cytokines. Ultimately, TCM enhance the immunocompetence of healthy person preventing infection.…”
Section: Tcm Prevents Infection For Healthy Personmentioning
confidence: 99%
“…Abundant Chinese medicinal formulae and Chinese patent medicine can effectively prevent healthy person from infection. As a number of studies have shown [12][13][14] , TCM can activate immune cells, improve phagocytosis and induce the production of cytokines. Ultimately, TCM enhance the immunocompetence of healthy person preventing infection.…”
Section: Tcm Prevents Infection For Healthy Personmentioning
confidence: 99%
“…Xinjiang ARPS can significantly enhance the level of influenza vaccine HI, specific IgG antibody, T cell subsets, lymphocyte proliferation, and cytokine secretion. At the same time, it can also significantly increase the level of dendritic cells (DCs) surface molecules, down-regulate the expression of Treg cells and enhance CTL responses ( Zhang et al, 2017a ). Xinjiang ARPS can also significantly increase the level of Foot-and-mouth Disease Vaccines (FMDV) IgG antibody, IgG 1 and IgG 2a subtypes, it has immune synergistic effect on commercial adjuvants of FMDV and long-term protective effect.…”
Section: The Adjuvant Effects On Vaccine Of Polysaccharides From Tcmmentioning
confidence: 99%
“…It is used to treat colds in folk medicine (32). Zhang et al (33) showed that the aqueous extract of A. rupestris could be an efficient adjuvant for influenza virus vaccines to boost immune responses and reduce the antigen doses required for triggering the immune system (33).…”
Section: Artemisia Rupestrismentioning
confidence: 99%